2011
DOI: 10.1016/j.neuroscience.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Periadolescent ethanol exposure reduces adult forebrain ChAT+IR neurons: correlation with behavioral pathology

Abstract: Substance abuse typically begins in adolescence; therefore, the impact of alcohol during this critical time in brain development is of particular importance. Epidemiological data indicate that excessive alcohol consumption is prevalent among adolescents and may have lasting neurobehavioral consequences. Loss of cholinergic input to the forebrain has been demonstrated following fetal alcohol exposure and in adults with Wernicke-Korsakoff syndrome. In the present study, immunohistochemistry for choline acetyltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 118 publications
(143 reference statements)
10
107
2
Order By: Relevance
“…Our AIE model was based on the characterization of adolescence that begins in the rat at PD 28 (Spear, 2000). Although other researchers have suggested that adolescence begins at a later time point, for example PD35 (Semple et al, 2013), our AIE model is consistent with previous research that has demonstrated adolescent specific deficits following EtOH exposure during PD28-PD55 (Ehlers et al, 2011; Broadwater and Spear, 2013; Vetreno et al, 2014; Vetreno and Crews, 2012). Additionally, our AIE model encompasses the peri-adolescent, early, mid and late adolescent periods that are in accordance with both Spear (2000) and Semple (2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our AIE model was based on the characterization of adolescence that begins in the rat at PD 28 (Spear, 2000). Although other researchers have suggested that adolescence begins at a later time point, for example PD35 (Semple et al, 2013), our AIE model is consistent with previous research that has demonstrated adolescent specific deficits following EtOH exposure during PD28-PD55 (Ehlers et al, 2011; Broadwater and Spear, 2013; Vetreno et al, 2014; Vetreno and Crews, 2012). Additionally, our AIE model encompasses the peri-adolescent, early, mid and late adolescent periods that are in accordance with both Spear (2000) and Semple (2013).…”
Section: Discussionsupporting
confidence: 91%
“…Although AIE leads to decreased neurogenesis within the hippocampus (Geil et al, 2014; Vetreno and Crews, 2015; Sakharkar et al, 2016), AIE’s detrimental effects on spatial memory are inconclusive (Risher et al, 2013; Swartzwelder et al, 2015; Beaudet et al, 2016). Following AIE, there is also a significant loss in the number of cholinergic neurons within the medial septum/diagonal band (MS/DB), which projects to the hippocampus, and the Nucleus basalis of Meynert (NbM) that projects to the cortex (Ehlers et al, 2011; Vetreno et al, 2014; Boutros et al, 2015). These effects are age-specific; there is no difference in cholinergic populations following adult binge exposure models (Vetreno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ehlers, Criado, Wills, Liu, & Crews (2011) found an increase in locomotor activity and a decrease in cholinergic neurons in Ch1–4 nuclei of the basal forebrain after adolescent ethanol exposure. There is also evidence of neuroinflammation and myelin disruption within the prefrontal cortex after chronic adolescent ethanol exposure in rats (Bava, Jacobus, Thayer, & Tapert, 2013; Pascual, Pla, Miñarro, & Guerri, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These data were then compared to previously published behavioral data (Ehlers et al, 2011, 2013a,b) on adult rats (PD70-107) that were exposed to 5 weeks of ethanol vapor or control (air) conditions during adolescence.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that chronic intermittent exposure to ethanol vapor during adolescence (14 hours exposure/10 hours no exposure, daily, over a 5-week period) can cause: increases in voluntary ethanol drinking, reductions in the size of the hippocampus as imaged by diffusion tensor imaging, reductions in measures of hippocampal neurogenesis, increases in the latency of the P300 component of the event-related potential, signs of behavioral disinhibition in the light/dark box and open field conflict test, immobility in the forced swim test, and reductions in cholinergic tone in the basal forebrain (see Criado and Ehlers, 2013; Ehlers et al, 2011, 2013a,b, 2014). …”
Section: Introductionmentioning
confidence: 99%